ҚАРАҚАЛПАҚ ЛЕКСИКОГРАФИЯСЫНДАҒЫ ЕКИ ТИЛЛИК АЎДАРМА СӨЗЛИКЛЕРДИҢ ДҮЗИЛИЎ ПРИНЦИПЛЕРИ - Мамбетмуратова, М.Т. (ILIM hám JÁMIYET, 2020)
In article paths of formation and development of the Karakalpak lexicography are considered. The review of principles of building of bilingual translation dictionaries in the Karakalpak tongue is made.